Kazakhstan-Iranian relations: achievements, problems, prospects - Kozhakhmetov, K. (Journal of Oriental Studies, 2016)
Article considered the political and economic relations between two states. Both states are members of the regional organizations, adhere to common positions on problems of regional security.